دور السياحة الصحية في تفعيل الاستثمار السياحي بالجزائر - Ghodbane, Rahma; Atoub, Karima (Finance and Business Economies Review, 2018)
As a result of the daily pressures experienced by members of the society in our time, which is characterized by high technology and the legacy, in addition to globalization and the resulting psychological and physical disorders that made individuals not looking for tourism for recreation and breaking the routine of the work of the killer, But see the transition from one country to another centers for treatment and physical comfort and rehabilitation to meet the conditions of life and the requirements of the times. Which makes medical or health tourism a win for many countries is the containment of the latter baths and resorts metal only, make them aware of this natural wealth, which made them an investment in the area of tourism through the restoration and restructuring in accordance with the requirements of modern life,thus Algeria contains many tourist areas. In particular, many mineral baths qualify as the source of the best types of services provided in the framework of health tourism such as Hammam Ghalema, Khanshla, Biskra, Tlagema, Hammam El Sokhna and others. Which has proved throughout the ages and its uniqueness mineral water in the treatment of many diseases, but being uninvited to become a tourist destination therapeutic and because of the attention to this natural wealth and exploitation and investment to promote the tourism sector made us raise the following main question: Is the reality of healthy tourism As one of the tourism investment in the Algerian indicators